Preparation process of high-performance Cu-Ni-Fe alloy calculated and designed based on first principle
By combining first-principles calculations and the CALPHAD method, a precise thermodynamic database for Cu-Ni-Fe alloys was constructed, and the composition and process parameters were optimized. This solved the problems of blind composition design and poor performance in the traditional Cu-Ni-Fe alloy preparation process, and achieved the stability and consistency of high-performance alloys to meet the needs of high-end applications.
Patent Information
- Application Number
- CN202610186909.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-02-10
- Publication Date
- 2026-03-17
- Estimated Expiration
- 2046-02-10
AI Technical Summary
Existing Cu-Ni-Fe alloy preparation processes suffer from problems such as blind composition design, insufficient accuracy of thermodynamic databases, single performance optimization, unreasonable process parameters, and poor overall performance. These issues result in large fluctuations in alloy performance, long development cycles, and high costs, making it difficult to meet the requirements of high-end fields such as marine engineering and aerospace.
By combining first-principles calculations with the CALPHAD method, a precise thermodynamic database for Cu-Ni-Fe ternary alloys is constructed. By calculating isothermal sections, vertical sections, and liquidus projection diagrams, the alloy composition is optimized. Combined with the addition of trace elements, the work function, elastic constant, and coefficient of thermal expansion of the alloy are optimized. The melting, heat treatment, and forming processing parameters are scientifically designed to achieve multi-objective synergistic optimization.
It achieves stability and consistency in alloy properties, with tensile strength ≥816.4MPa, total elongation at break ≥34.27%, corrosion resistance improved by more than 30%, thermal expansion coefficient matched to the needs of different application scenarios, product qualification rate reached 98%, R&D cycle shortened to 3-4 months, and cost reduced by 40%-50%.
Smart Images

Figure CN121674758A_ABST
Abstract
Description
TECHNICAL FIELD
[0001] The present application relates to the technical field of alloy material preparation, and particularly relates to a preparation process of a high-performance Cu-Ni-Fe alloy based on first-principle calculation design, and is especially suitable for the fields of marine engineering, electronic packaging, aerospace, precision machinery and the like which have strict requirements on mechanical properties, thermal stability and corrosion resistance. BACKGROUND
[0002] As an important multi-component alloy material, the Cu-Ni-Fe alloy has high electrical conductivity of copper, corrosion resistance of nickel and high strength of iron, and has an irreplaceable position in the industrial field. In marine engineering, the alloy can be used to manufacture ship propellers, seawater desalination equipment and offshore platform structural parts which need to resist corrosion in high-salt and high-humidity environments; in the field of electronic packaging, the alloy needs to have a thermal expansion coefficient matching the chip to avoid packaging failure caused by temperature cycling; in the field of aerospace, the alloy needs to maintain stable mechanical properties in a wide temperature range (-50℃-800℃) to meet the load-bearing requirements of structural parts; in the field of precision machinery, the alloy needs to have high strength and good plasticity to ensure the machining precision and service life of parts.
[0003] With the rapid development of industrial technology, the comprehensive performance requirements of the Cu-Ni-Fe alloy are increasingly improved, not only the single performance index needs to be optimized, but also the strength, plasticity, corrosion resistance, thermal stability and processing performance need to be synergistically improved. However, the traditional preparation process of the Cu-Ni-Fe alloy has many technical bottlenecks, which seriously restricts the performance upgrading and application expansion of the Cu-Ni-Fe alloy.
[0004] Firstly, the traditional composition design relies on the experience trial-and-error method and lacks scientific thermodynamic theory support. In the prior art, the alloy composition design is mostly based on the experience accumulation of engineers or the simple performance prediction of binary alloys, without fully considering the interaction of elements in the ternary system and the influence of temperature on phase equilibrium. Due to the incomplete phase diagram data of the Cu-Ni-Fe ternary alloy, especially the lack of accurate data of isothermal section, vertical section and liquidus projection in the key application temperature range of 873K-1423K, the composition design is highly blind. For example, some processes blindly increase the Fe content to pursue high strength, which leads to increased brittleness of the alloy and insufficient elongation at break of less than 20%; while excessively increasing the Cu content can improve the electrical conductivity, but will reduce the corrosion resistance and high-temperature stability of the alloy, which cannot meet the strict requirements of marine engineering or aerospace. This experience-based design mode not only leads to large fluctuations in alloy performance, but also needs to consume a large amount of manpower and material resources for multiple tests, with a long research and development cycle (usually 6-12 months) and high research and development cost.
[0005] Secondly, the existing thermodynamic database has the problem of insufficient accuracy. The CALPHAD (Calculation of Phase Diagrams) method is the core tool for alloy thermodynamic design, but traditional databases rely on single-source experimental data, do not systematically evaluate data reliability, and lack experimental verification of key phase diagram data. For example, for the Gibbs free energy model parameters of the (γFe, Ni) phase and the (Cu, Ni) phase in the Cu-Ni-Fe ternary alloy, the existing database mostly uses default values or simple fitting, with a large deviation (up to 5%-10%) from actual experimental results. This leads to the calculated phase diagram based on the database failing to accurately reflect the phase equilibrium state of the alloy at different temperatures and compositions, and further causing the composition design to be disconnected from the actual performance. In addition, traditional databases do not cover the influence of trace elements (such as Ti, Zr, Mg) on the phase structure, limiting the space for optimizing alloy performance by adding trace elements.
[0006] Thirdly, the alloy performance optimization lacks a multi-objective collaborative design concept. Traditional processes often only focus on improving a single performance indicator, such as improving strength through solid solution strengthening, while ignoring the regulation of key performance indicators such as thermal expansion coefficient and corrosion resistance. For example, existing technologies improve corrosion resistance by increasing Ni content, but excessive addition of Ni will cause the thermal expansion coefficient to increase (more than 20×10 -6 / K), which does not match the thermal expansion coefficient of ceramic substrates used in electronic packaging (6×10 -6 / K-10×10 -6 / K), leading to thermal stress cracks during packaging. When improving strength through cold rolling, if the heat treatment parameters are not optimized, the alloy plasticity will decrease, and the total elongation at break will be less than 25%. In addition, traditional processes do not accurately regulate essential performance parameters such as the work function and elastic constant of the alloy through first-principles calculations, and cannot optimize the electronic structure and mechanical properties of the alloy at the atomic level, resulting in poor overall performance of the alloy.
[0007] Fourthly, the preparation process parameters lack scientific optimization basis. The selection of melting and subsequent processing parameters mostly relies on experience and does not consider the thermodynamic characteristics and phase diagram data of the alloy. For example, traditional melting temperatures are mostly set at 1600K-1800K, but are not adjusted according to the specific composition of the alloy, leading to phenomena such as overburning or incomplete melting of some compositions. The temperature and holding time of the heat treatment process are chosen arbitrarily without considering the phase transition temperature of the alloy, resulting in uneven alloy organization (grain size deviation can reach 30%-50%) and poor performance stability. In addition, during the forming process, the rolling temperature and reduction ratio are not reasonably matched, such as using large reduction ratio rolling at low temperature, which can cause residual stress in the alloy and reduce fatigue life.
[0008] Fifth, the overall performance of existing Cu-Ni-Fe alloys is poor, making it difficult to meet the requirements of high-performance alloys in fields such as marine engineering and aerospace. For example, in deep-sea environments, existing alloys have insufficient corrosion resistance, with a service life of only 3-5 years; in aero-engine blade applications, their high-temperature mechanical properties are unstable, with tensile strength decreasing by more than 30% at temperatures above 800K. In addition, the performance of existing alloys fluctuates significantly (performance deviations within the same batch of products can reach 10%-15%), failing to meet the consistency requirements of the precision machinery field.
[0009] In summary, existing Cu-Ni-Fe alloy preparation processes suffer from problems such as blind composition design, insufficient precision in thermodynamic databases, limited performance optimization, unreasonable process parameters, and poor overall performance. There is an urgent need to develop a high-performance Cu-Ni-Fe alloy preparation process based on scientific theory guidance, precise design, and multi-objective synergistic optimization to overcome existing technological bottlenecks and expand its application in high-end fields. Summary of the Invention
[0010] This invention aims to solve the following technical problems existing in the current Cu-Ni-Fe alloy preparation process:
[0011] 1. The design of components relies on trial and error based on experience and lacks the support of thermodynamic theory, resulting in large performance fluctuations, long R&D cycles, and high costs;
[0012] 2. Existing thermodynamic databases lack sufficient accuracy, key phase diagram data have not been experimentally verified, and model parameters are not accurately fitted, thus failing to provide a reliable basis for composition design;
[0013] 3. Performance optimization lacks multi-objective collaborative design, focusing only on a single performance index and neglecting the synergistic improvement of properties such as strength, plasticity, thermal stability, and corrosion resistance;
[0014] 4. Inappropriate selection of smelting, heat treatment and forming process parameters, without considering the thermodynamic properties of the alloy, leads to uneven alloy structure and poor performance stability;
[0015] 5. Existing alloys have poor overall performance, and key indicators such as tensile strength, elongation at break, and coefficient of thermal expansion cannot meet the requirements of high-end applications.
[0016] To solve the above-mentioned technical problems, the present invention adopts the following technical solution:
[0017] A preparation process for a high-performance Cu-Ni-Fe alloy based on first-principles calculations includes the following steps:
[0018] (1) Thermodynamic design: First-principles combined with CALPHAD method was used to collect Cu-Fe, Fe-Ni, Cu-Ni binary phase diagram data, thermochemical experimental data and thermodynamic basic data, evaluate the reliability of the data and verify the key phase diagram data through experiments, select the Gibbs free energy model, optimize thermodynamic parameters, and establish Cu-Ni-Fe ternary alloy thermodynamic database.
[0019] (2) Composition determination: Based on the thermodynamic database, the isothermal cross section, the vertical cross section and liquidus projection diagram of the Cu-Ni-Fe ternary alloy in the temperature range of 873K-1423K were calculated. The alloy composition range was initially determined to be: Cu atomic percentage 20%-80%, Ni atomic percentage 5%-40%, and Fe atomic percentage 5%-40%.
[0020] (3) Performance optimization: The work function, elastic constant and thermal expansion coefficient of the alloy are calculated by first principle calculation, and the composition is adjusted based on the calculation results to determine the final alloy composition;
[0021] (4) Melting and preparation: The raw materials are proportioned according to the final alloy composition, and the raw materials are melted using a melting process to prepare alloy ingots;
[0022] (5) Subsequent processing: The alloy ingot is subjected to heat treatment and forming processing in sequence to obtain a high-performance Cu-Ni-Fe alloy.
[0023] Furthermore, in step (1), the Gibbs free energy model is a sub-regular solution model, and the thermodynamic parameter optimization includes fitting the model parameters of the liquid phase (L), (αFe) phase, (γFe, Ni) phase and (Cu, Ni) phase.
[0024] Furthermore, in step (2), the alloy composition range is initially determined to be: Cu atomic percentage 30%-75%, Ni atomic percentage 10%-30%, and Fe atomic percentage 10%-30%.
[0025] Furthermore, in step (3), the work function of the alloy calculated by the first principle is in the range of 4.5eV-5.5eV, and the work function is the difference between the vacuum energy level and the Fermi level.
[0026] Further, in step (3), the calculation of the coefficient of thermal expansion includes: constructing 11 alloy structure files with a scaling factor of 0.95-1.05, calculating the entropy, enthalpy, free energy, and heat capacity data in the temperature range of 300K-2000K using first-principles calculations, and determining that the coefficient of thermal expansion of the alloy in the temperature range of 300K-1200K is <20×10⁻⁶. -6 / K.
[0027] Further, in step (3), the elastic constants satisfy: bulk modulus K is 140GPa-190GPa, shear modulus G is 35GPa-120GPa, Young's modulus E is 90GPa-160GPa, and Poisson's ratio ν is 0.35-0.40.
[0028] Furthermore, in step (4), the smelting process adopts vacuum arc smelting or induction smelting, the smelting temperature is 1400K-1800K, argon or nitrogen is introduced for protection during smelting, and the temperature is held for 10min-30min after melting before casting; the raw materials also contain 0.1%-2% atomic percentage trace elements, which are one or more of Ti, Zr or Mg.
[0029] Further, in step (5), the heat treatment process is as follows: heat treatment at 873K-1273K for 1h-6h, and after heat treatment, the furnace is cooled to room temperature or air-cooled to room temperature.
[0030] Furthermore, in step (5), the forming process is rolling, forging or extrusion, wherein the rolling temperature is 800K-1200K and the reduction is 30%-70%.
[0031] Furthermore, the high-performance Cu-Ni-Fe alloy has a tensile strength ≥816.4MPa and a total elongation at break ≥34.27%.
[0032] The preparation process of this invention, through the deep integration of first-principles calculations and the CALPHAD method, achieves precise design and efficient preparation of Cu-Ni-Fe alloys, and has the following significant advantages compared with existing technologies:
[0033] 1. The thermodynamic database is accurate and reliable, laying the scientific foundation for composition design.
[0034] Existing thermodynamic databases often rely on single-source data without systematic verification, leading to significant deviations in phase diagram calculations and failing to provide reliable support for composition design. This invention combines first-principles calculations with the CALPHAD method. First, it systematically collects binary phase diagrams, thermochemical, and thermodynamic data from multiple sources. Anomalies are eliminated through error analysis and experimental verification (such as DTA and XRD) to ensure the accuracy of the basic data. Then, a sub-regular solution model is selected to accurately fit the model parameters for the liquid (L), (αFe), (γFe, Ni), and (Cu, Ni) phases, keeping the deviation between the calculated phase diagram and experimental data within 2%. For example, for the isothermal section of a Cu-Ni-Fe ternary alloy at 1073 K, the deviation between the (Cu, Ni) phase region calculated by this invention and the experimental result is only 1.2%, far lower than the 5%-10% deviation of existing databases. A precise thermodynamic database can accurately reflect the phase equilibrium state of alloys at different temperatures and compositions, avoiding the blindness of traditional composition design, providing a scientific basis for subsequent composition optimization, shortening the R&D cycle to 3-4 months, and reducing R&D costs by 40%-50%.
[0035] 2. Scientifically and precisely designed composition ensures stable alloy performance.
[0036] Existing technologies rely on trial and error in composition design, leading to large fluctuations in alloy properties, with performance deviations of up to 10%-15% within the same batch of products. This invention, based on a precise thermodynamic database, systematically analyzes phase region distribution and phase transformation laws by calculating isothermal sections, vertical sections, and liquidus projection diagrams within the 873K-1423K temperature range, initially determining a reasonable composition range. Then, by calculating essential performance parameters such as work function, elastic constants, and coefficient of thermal expansion using first-principles calculations, the composition is fine-tuned, achieving multi-objective synergistic optimization. For example, for marine engineering applications, a Cu 60%, Ni 20%, Fe 20% (atomic percentage) alloy is designed with a work function of 5.2 eV, exhibiting corrosion resistance more than 30% higher than existing alloys; for electronic packaging applications, a Cu 70%, Ni 15%, Fe 15% (atomic percentage) alloy is designed with a coefficient of thermal expansion of 12 × 10⁻⁶. -6 / K exhibits good compatibility with ceramic substrates. The composition design method of this invention ensures that the alloy maintains stable performance in different application scenarios, with performance deviations within the same batch of products controlled within 5%, significantly superior to existing technologies.
[0037] 3. Excellent overall performance and synergy, meeting the needs of high-end applications.
[0038] Existing alloys often focus on only a single performance indicator, resulting in poor overall performance, such as tensile strength less than 500 MPa, elongation at break less than 30%, and mismatched coefficients of thermal expansion. This invention achieves a synergistic improvement in strength, plasticity, corrosion resistance, and thermal stability through multi-objective performance optimization. First, through composition optimization and the addition of trace elements, the alloy achieves a tensile strength ≥816.4 MPa and a total elongation at break ≥34.27%, combining high strength with good plasticity. Second, through work function optimization (4.5 eV-5.5 eV), the risk of galvanic corrosion is reduced, and salt spray corrosion resistance is improved by more than 25% compared to existing alloys. Third, through control of the coefficient of thermal expansion (less than 20 × 10⁻⁶), the overall performance is improved. -6 / K), to meet the thermal matching requirements of different application scenarios; finally, the optimization of elastic constants gives the alloy good stiffness and toughness, with a Young's modulus of 90GPa-160GPa, which can withstand complex loads.
[0039] 4. The preparation process is stable and controllable, improving product consistency.
[0040] Existing technologies rely on empirically selected melting, heat treatment, and forming parameters, resulting in uneven alloy microstructure and large performance fluctuations. The preparation process parameters of this invention are scientifically determined based on thermodynamic databases and performance calculations: the melting temperature is adjusted according to the alloy liquidus temperature (1400K-1800K), and a holding time of 10-30 minutes ensures thorough mixing of the raw materials; the heat treatment temperature (873K-1273K) and holding time (1h-6h) are matched to the alloy phase transformation temperature, effectively eliminating residual stress and ensuring uniform grain size (deviation ≤10%); during forming, the optimized combination of rolling temperature (800K-1200K) and reduction (30%-70%) further refines the grains and improves microstructure density. For example, using process parameters such as vacuum arc melting (1600K, holding for 20min), heat treatment (1073K, holding for 3h, furnace cooling), and rolling (1000K, 50% reduction), the prepared Cu 50%, Ni 25%, Fe 25% (atomic percentage) alloy has a grain size concentrated in the range of 20μm-30μm, a microstructure density ≥99.5%, and a product qualification rate of over 98%, which is far higher than the 90% qualification rate of existing technologies.
[0041] 5. It has a wide range of applications and significant industrialization value.
[0042] Existing alloys offer limited performance and applicability, failing to meet the personalized needs of diverse fields. This invention, through flexible adjustment of composition and process parameters, can prepare high-performance Cu-Ni-Fe alloys suitable for various scenarios: in marine engineering, increasing Ni content (25%-30%) and adding Ti (0.5%-1%) enhances corrosion resistance; in electronic packaging, increasing Cu content (65%-75%) and optimizing the coefficient of thermal expansion (10×10⁻⁶) improves performance. -6 / K-15×10 -6 / K), improving electrical conductivity and thermal matching; in the field of precision machinery, increasing the Fe content (25%-30%) and using forging processes enhances strength and machining accuracy; in the aerospace field, adding Zr (1%-2%) and optimizing high-temperature heat treatment processes improves high-temperature stability. Furthermore, the preparation process of this invention uses conventional melting and processing equipment, requiring no special customization, exhibiting strong process compatibility, facilitating industrial-scale production, and reducing production costs by 15%-20% compared to existing technologies, demonstrating significant economic value and market competitiveness. Attached Figure Description
[0043] Figure 1 The CALPHAD calculation flowchart illustrates the steps involved in building a thermodynamic database: data collection → reliability assessment → experimental verification → model selection → parameter optimization → database establishment.
[0044] Figures 2-6 Isothermal cross-section diagram of Cu-Ni-Fe ternary alloy, showing the distribution of (Cu, Ni) phase, (γFe, Ni) phase, (αFe) phase, and liquidus region. Figure 2 The isothermal cross-sectional phase diagram of the Cu-Ni-Fe ternary alloy at 1423 K is shown. Figure 3 The isothermal cross-sectional phase diagram of the Cu-Ni-Fe ternary alloy at 1273 K is shown. Figure 4 The isothermal cross-sectional phase diagram of the Cu-Ni-Fe ternary alloy at 1123 K is shown. Figure 5 The isothermal cross-sectional phase diagram of the Cu-Ni-Fe ternary alloy at 1073 K is shown. Figure 6 The isothermal cross-sectional phase diagram of the Cu-Ni-Fe ternary alloy at 873 K;
[0045] Figures 7-11 The vertical cross-sectional diagram of the Cu-Ni-Fe ternary alloy illustrates the influence of temperature and composition on the phase composition. Figure 7 For (Cu 50 Fe 50 ) 1-x -Ni x System diagram, Figure 8 For (Cu 75 Ni 25 )1-x -Fe x System diagram, Figure 9 Cu x -(Fe 75 Ni 25 ) 1-x System diagram, Figure 10 Cu x -(Fe 50 Ni 50 ) 1-x System diagram, Figure 11 Diagram of the 40 at.% Ni system;
[0046] Figure 12 Projection diagram of the liquidus line of a Cu-Ni-Fe ternary alloy, showing the relationship between liquidus temperature and composition;
[0047] Figure 13 The work function calculation diagram of the alloy shows the work function values of different surfaces (100), (110), and (111), where the work function of the target alloy is 4.5eV-5.5eV. Detailed Implementation
[0048] The specific embodiments of the present invention will be described in detail below with reference to the accompanying drawings and examples, so as to better understand the technical solution of the present invention.
[0049] A preparation process for a high-performance Cu-Ni-Fe alloy based on first-principles calculations includes the following steps:
[0050] (a) Thermodynamic Design
[0051] like Figure 1 As shown, a precise thermodynamic database for Cu-Ni-Fe ternary alloys is constructed using a combination of first-principles calculations and the CALPHAD method. Specific steps include:
[0052] 1. Data Collection: The system collects binary phase diagram data of Cu-Fe, Fe-Ni, and Cu-Ni (including liquidus and solidus temperatures, phase region ranges, etc.), thermochemical experimental data (such as enthalpy of formation, entropy of mixing, etc.), and fundamental thermodynamic data (such as specific heat capacity and melting point of elements, etc.). Data sources include authoritative domestic and international databases (such as Thermo-Calc and JMatPro), academic literature, and industry standards.
[0053] 2. Data Reliability Assessment: Error analysis and consistency checks are used to assess the reliability of the collected data, and abnormal data with large deviations (deviations exceeding 5%) are removed. For key phase diagram data (such as the equilibrium temperatures of the (γFe, Ni) and (Cu, Ni) phases), experiments such as differential thermal analysis (DTA) and X-ray diffraction (XRD) are used to verify the data accuracy.
[0054] 3. Model selection: The sub-regular solution model was selected as the Gibbs free energy model. This model can accurately describe the interatomic interactions in multi-component alloys and is suitable for multiphase systems of Cu-Ni-Fe ternary alloys.
[0055] 4. Parameter optimization: Based on the validated experimental data, the least squares method was used to fit the model parameters of the liquid phase (L), (αFe) phase, (γFe, Ni) phase and (Cu, Ni) phase. The optimized parameters can control the deviation between the calculated phase diagram and the experimental data within 2%, and finally establish a Cu-Ni-Fe ternary alloy thermodynamic database.
[0056] (II) Determination of Components
[0057] Based on the aforementioned thermodynamic database, the Thermo-Calc software was used to calculate the isothermal cross-sectional diagrams of the Cu-Ni-Fe ternary alloy in the temperature ranges of 873 K, 1073 K, 1123 K, 1273 K, and 1423 K (e.g., ...). Figures 2-6 As shown), and a vertical cross-sectional view of the preset composition system (including (Cu) 50 Fe 50 ) 1-x -Ni x 、(Cu 75 Ni 25 ) 1-x -Fe x Cu x -(Fe 75 Ni 25 ) 1-x Cu x -(Fe 50 Ni 50 ) 1-x and the 40 at.% Ni system, such as Figures 7-11 (as shown) and liquidus projection diagram (as shown) Figure 12 (As shown). By analyzing the phase region distribution, equilibrium phase composition, and phase transformation law in the phase diagram, the preliminary alloy composition range is determined to be: Cu atomic percentage 20%-80%, Ni atomic percentage 5%-40%, and Fe atomic percentage 5%-40%. This composition range ensures that the alloy mainly forms a two-phase structure of (Cu, Ni) solid solution and (γFe, Ni) solid solution within the target temperature range, avoiding the formation of brittle phases (such as Fe3Cu).
[0058] (III) Performance Optimization
[0059] The key performance parameters of the alloy were accurately calculated using first-principles calculations (based on density functional theory and using VASP software). The composition was then adjusted based on the calculation results to determine the final alloy composition, specifically including:
[0060] 1. Work function calculation: Construct a Slab model of the alloy, simulate the material surface, perform structural optimization, and calculate the difference between the vacuum energy level and the Fermi level (i.e., the work function). The work function range is controlled between 4.5 eV and 5.5 eV (e.g., ...). Figure 13 (As shown). The magnitude of the work function indicates the strength of electron binding in a metal. A work function within this range can reduce the risk of galvanic corrosion between the alloy and the surrounding medium, thus improving corrosion resistance.
[0061] 2. Calculation of Elastic Constants: Calculate the bulk modulus K, shear modulus G, Young's modulus E, and Poisson's ratio ν of the alloy, where K is 140 GPa-190 GPa, G is 35 GPa-120 GPa, E is 90 GPa-160 GPa, and ν is 0.35-0.40. See the following alloy elastic constant moments, including the elastic constant matrices of Cu and FeNi3 and the calculated results of bulk modulus, shear modulus, Young's modulus, and Poisson's ratio:
[0062] The elastic constant matrix of Cu:
[0063]
[0064]
[0065] Bulk modulus: K≈149.3GPa;
[0066] Shear modulus: pure shear = 90.09 GPa, engineering average G≈35.2 GPa;
[0067] Young's modulus: E≈98.5GPa;
[0068] Poisson's ratio: ν≈0.39.
[0069] The elastic constant matrix of FeNi3:
[0070]
[0071]
[0072] The bulk modulus K ≈ 184.2 GPa;
[0073] Shear modulus: pure shear G = 119.3 GPa, engineering average Gaavg ≈ 55.8 GPa;
[0074] Young's modulus E≈152.4GPa;
[0075] Poisson's ratio ν≈0.363.
[0076] The elastic constant is the essential manifestation of the mechanical properties of an alloy, and the range of this parameter can ensure that the alloy has both good strength and toughness.
[0077] 3. Calculation of Coefficient of Thermal Expansion: Eleven alloy structure files with scaling factors ranging from 0.95 to 1.05 (scaling factors of 0.95, 0.96, 0.97, 0.98, 0.99, 1.00, 1.01, 1.02, 1.03, 1.04, and 1.05 respectively) were constructed. Entropy, enthalpy, free energy, and heat capacity data within the temperature range of 300K-2000K were calculated using first-principles calculations. The coefficient of thermal expansion of the alloy in the temperature range of 300K-1200K was determined to be <20 × 10⁻⁶. -6 / K, enabling it to match the thermal expansion requirements of different application scenarios;
[0078] 4. Composition Adjustment: Based on the calculation results of the above performance parameters, the initially determined composition range was fine-tuned, and the final atomic percentage composition of the alloy was determined to be: Cu 30%-75%, Ni 10%-30%, Fe 10%-30%.
[0079] (iv) Smelting and preparation
[0080] 1. Raw material preparation: The raw materials are proportioned according to the final alloy composition. The raw materials are Cu powder, Ni powder, and Fe powder with a purity of ≥99.95%. At the same time, 0.1%-2% of trace elements (one or more of Ti, Zr, or Mg) are added. Trace elements can refine the grains and improve the strength and corrosion resistance of the alloy.
[0081] 2. Melting process: Vacuum arc melting or induction melting is adopted, and the melting temperature is controlled at 1400K-1800K. Argon or nitrogen gas is introduced during melting to protect the raw materials and prevent oxidation. After melting, the temperature is held for 10min-30min to ensure that the raw materials are fully mixed and uniform. Then, it is poured into the mold to prepare alloy ingots.
[0082] (v) Subsequent processing
[0083] 1. Heat treatment: Hold the alloy ingot at 873K-1273K for 1-6 hours. After holding, cool it to room temperature with the furnace or air cool it to room temperature. Heat treatment eliminates residual stress inside the ingot, homogenizes the microstructure, and improves performance stability.
[0084] 2. Forming and processing: The heat-treated ingots are formed and processed by rolling, forging or extrusion. The rolling temperature is 800K-1200K and the reduction is 30%-70%. The forming and processing further refines the grains, improves the strength and plasticity of the alloy, and finally obtains a high-performance Cu-Ni-Fe alloy.
[0085] To make the present invention more fully disclosed, more specific embodiments are described below.
[0086] Example 1
[0087] A preparation process for a high-performance Cu-Ni-Fe alloy based on first-principles calculations includes the following steps:
[0088] (a) Thermodynamic Design
[0089] 1. Data collection: Collect Cu-Fe, Fe-Ni, and Cu-Ni binary phase diagram data (including liquidus temperature, solidus temperature, phase region boundaries, etc.), thermochemical experimental data (enthalpy of formation, entropy of mixing), and basic thermodynamic data (specific heat capacity, melting point). The data are sourced from the Thermo-Calc database, the "Handbook of Binary Alloy Phase Diagrams", and relevant academic literature.
[0090] 2. Data Validation: The solidus temperature of the (Cu, Ni) phase was verified by differential thermal analysis (DTA), and the experimental results deviated from the literature data by 1.5%. The lattice constant of the (γFe, Ni) phase was verified by X-ray diffraction (XRD), and the deviation was 0.8%, ensuring the reliability of the data.
[0091] 3. Model Selection and Parameter Optimization: A subnormal solution model was used to fit the model parameters for the liquid (L), (αFe), (γFe, Ni) and (Cu, Ni) phases. The optimized parameters are as follows:
[0092] Liquid phase (L):
[0093]
[0094] (Cu, Ni) phase:
[0095]
[0096] (γFe, Ni) phase:
[0097]
[0098] (αFe) phase:
[0099]
[0100] 3. Establish a database: Based on the above parameters, establish a thermodynamic database for Cu-Ni-Fe ternary alloys.
[0101] (II) Determination of Components
[0102] Thermo-Calc software was used to calculate the isothermal cross-sectional diagrams of the Cu-Ni-Fe ternary alloy at 873 K, 1073 K, 1273 K, and 1423 K (e.g., Figures 2-6 (as shown), and (Cu) 50 Fe 50 ) 1-x -Ni x Vertical section diagram (e.g.) Figure 7 (as shown) and liquidus projection diagram (as shown) Figure 12 (As shown). Analysis of the phase diagram shows that when the Cu atomic percentage is 50%, Ni atomic percentage is 25%, and Fe atomic percentage is 25%, the alloy mainly forms a (Cu, Ni) and (γFe, Ni) dual-phase structure in the temperature range of 873K-1423K, with no brittle phase forming. This composition has been preliminarily identified as a candidate composition.
[0103] (III) Performance Optimization
[0104] 1. Work function calculation: The work function Cu is constructed using VASP software. 50 Ni 25 Fe 25 The Slab model of the alloy, with a vacuum layer thickness of 15 Å, was used to calculate the work function after structural optimization. The result was 5.1 eV, which is within the optimization range of 4.5 eV-5.5 eV.
[0105] 2. Calculation of elastic constants: The calculated bulk modulus K = 165 GPa, shear modulus G = 78 GPa, Young's modulus E = 125 GPa, and Poisson's ratio ν = 0.38, which meet the requirements for elastic constants.
[0106] 3. Calculation of thermal expansion coefficient: Eleven alloy structure files with scaling from 0.95 to 1.05 were constructed. Entropy, enthalpy, free energy, and heat capacity data were calculated within the temperature range of 300K-2000K. The thermal expansion coefficient for the temperature range of 300K-1200K was determined to be 15 × 10⁻⁶. -6 / K, meets the requirements;
[0107] 4. Composition determination: The performance parameters of the candidate composition all meet the optimization requirements, and it is determined to be the final alloy composition (Cu 50%, Ni 25%, Fe 25%, atomic percentage).
[0108] (iv) Smelting and preparation
[0109] 1. Raw material preparation: Cu powder, Ni powder and Fe powder with a purity of 99.99% are used, and they are mixed in an atomic percentage ratio of 50:25:25. At the same time, Ti element with an atomic percentage of 0.8% is added. The total mass of raw materials is 500g.
[0110] 2. Melting process: Vacuum arc melting is adopted, with a vacuum degree ≤5×10 -3 Pa, melting temperature 1600K, argon gas protection (purity 99.99%), hold at the temperature for 20 minutes after melting, and cast into a graphite mold to prepare an alloy ingot with a diameter of 50mm and a length of 100mm.
[0111] (v) Subsequent processing
[0112] 1. Heat treatment: Place the alloy ingot into a box-type resistance furnace and hold it at 1073K for 3 hours. After holding, cool it to room temperature with the furnace.
[0113] 2. Forming and processing: Hot rolling process is adopted, with a rolling temperature of 1000K and a reduction of 50%, to obtain an alloy sheet with a thickness of 10mm after rolling.
[0114] (vi) Performance Testing
[0115] 1. Mechanical properties: Tensile tests were conducted using a universal testing machine. The tensile strength was 896.3 MPa, and the total elongation at break was 42.16%.
[0116] 2. Corrosion resistance: Salt spray corrosion test (5% NaCl solution, temperature 35℃, time 1000h) showed a corrosion rate of 0.02 mm / a, which is 33.3% higher than the existing alloy (0.03 mm / a).
[0117] 3. Coefficient of thermal expansion: Tested using a thermal expansion meter, the coefficient of thermal expansion in the temperature range of 300K-1200K is 15×10⁻⁶. -6 / K.
[0118] Example 2
[0119] A preparation process for a high-performance Cu-Ni-Fe alloy based on first-principles calculations includes the following steps:
[0120] (a) Thermodynamic Design
[0121] The same thermodynamic database as in Example 1 is used, so there is no need to rebuild it.
[0122] (II) Determination of Components
[0123] Based on a thermodynamic database, calculate Cu x -(Fe 50 Ni 50 ) 1-xVertical section diagram (e.g.) Figure 10 As shown in the figure, analysis shows that when the atomic percentage of Cu is 70%, the atomic percentage of Ni is 15%, and the atomic percentage of Fe is 15%, the alloy is a single (Cu, Ni) solid solution phase in the temperature range of 300K-800K, with a low coefficient of thermal expansion, which is suitable for electronic packaging applications. This composition has been preliminarily determined as a candidate composition.
[0124] (III) Performance Optimization
[0125] 1. Work function calculation: A Slab model was constructed for calculation, and the work function was 4.8 eV, which meets the requirements;
[0126] 2. Calculation of elastic constants: bulk modulus K = 149 GPa, shear modulus G = 65 GPa, Young's modulus E = 105 GPa, Poisson's ratio ν = 0.39, which meets the requirements;
[0127] 3. Calculation of thermal expansion coefficient: Based on first-principles calculations, the thermal expansion coefficient in the temperature range of 300K-1200K is 12×10⁻⁶. -6 / K has good compatibility with ceramic substrates;
[0128] 4. Composition determination: Determine the final alloy composition (Cu 70%, Ni 15%, Fe 15%, atomic percentage).
[0129] (iv) Smelting and preparation
[0130] 1. Raw material preparation: Use Cu powder, Ni powder and Fe powder with a purity of 99.99% in an atomic percentage ratio of 70:15:15, and add 0.5% Mg element. The total mass of raw materials is 500g.
[0131] 2. Melting process: Induction melting is adopted, the melting temperature is 1500K, nitrogen gas is introduced for protection, the temperature is held for 15 minutes, and then cast into a copper mold to prepare an ingot with a diameter of 50mm and a length of 100mm.
[0132] (v) Subsequent processing
[0133] 1. Heat treatment: Hold at 973K for 4 hours, then air cool to room temperature;
[0134] 2. Forming and processing: The cold rolling process is adopted, with a rolling temperature of 800K and a reduction of 40%, to obtain an alloy sheet with a thickness of 8mm.
[0135] (vi) Performance Testing
[0136] 1. Mechanical properties: Tensile strength 816.4 MPa, total elongation at break 38.29%;
[0137] 2. Coefficient of thermal expansion: 12 × 10⁻⁶ in the temperature range of 300K-800K.-6 / K, with an Al2O3 ceramic substrate (thermal expansion coefficient 8×10⁻⁶). -6 / K) matches well;
[0138] 3. Conductivity: The conductivity at room temperature is 45% IACS, which meets the requirements of electronic packaging.
[0139] Example 3
[0140] A preparation process for a high-performance Cu-Ni-Fe alloy based on first-principles calculations includes the following steps:
[0141] (a) Thermodynamic Design
[0142] The same thermodynamic database as in Example 1 was used.
[0143] (II) Determination of Components
[0144] Calculate the vertical cross-sectional diagram of the 40 at.% Ni system (e.g.) Figure 11 As shown in the figure, analysis shows that when the atomic percentages of Cu, Ni, and Fe are 30%, the alloy has high strength and is suitable for precision machinery applications. This composition has been preliminarily identified as a candidate composition.
[0145] (III) Performance Optimization
[0146] 1. Work function calculation: The work function is 5.4 eV, which meets the requirements;
[0147] 2. Calculation of elastic constants: bulk modulus K = 184 GPa, shear modulus G = 110 GPa, Young's modulus E = 155 GPa, Poisson's ratio ν = 0.36, indicating excellent strength;
[0148] 3. Calculation of thermal expansion coefficient: 18 × 10⁻⁶ for the temperature range of 300K-1200K. -6 / K, meeting machining requirements;
[0149] 4. Composition determination: Determine the final alloy composition (Cu 30%, Ni 30%, Fe 40%, atomic percentage).
[0150] (iv) Smelting and preparation
[0151] 1. Raw material preparation: Use Cu powder, Ni powder and Fe powder with a purity of 99.99% in an atomic percentage ratio of 30:30:40, and add Zr element with an atomic percentage of 1.5%. The total mass of raw materials is 500g.
[0152] 2. Melting process: Vacuum arc melting, temperature 1700K, argon protection, holding for 25 minutes, then casting into a graphite mold to prepare an ingot.
[0153] (v) Subsequent processing
[0154] 1. Heat treatment: Hold at 1173K for 2 hours, then air cool to room temperature;
[0155] 2. Forming and processing: Forging process is adopted, forging temperature is 1100K, deformation is 60%, and forging is obtained.
[0156] (vi) Performance Testing
[0157] 1. Mechanical properties: tensile strength 982.1 MPa, total elongation at break 34.27%;
[0158] 2. Hardness: Brinell hardness HB185, 20% higher than existing alloys;
[0159] 3. Wear resistance: Coefficient of friction 0.35, wear amount 0.01mm 3 It has excellent wear resistance.
[0160] The above embodiments are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., without departing from the spirit and principle of the present invention should be included within the protection scope of the present invention.
Claims
1. A process for preparing a high-performance Cu-Ni-Fe alloy designed based on first-principle calculation, characterized in that, The method comprises the following steps: (1) thermodynamic design: adopting first principle combining with CALPHAD method, collecting Cu-Fe, Fe-Ni, Cu-Ni binary phase diagram data, thermochemical experimental data and thermodynamic basic data, evaluating data reliability and verifying key phase diagram data through experiment, selecting Gibbs free energy model, optimizing thermodynamic parameters, and establishing Cu-Ni-Fe ternary alloy thermodynamic database; (2) composition determination: based on the thermodynamic database, calculating isothermal section of Cu-Ni-Fe ternary alloy in 873K-1423K temperature range, vertical section of preset composition system and liquidus projection diagram, and preliminarily determining alloy composition range as follows: atomic percentage of Cu is 20%-80%, atomic percentage of Ni is 5%-40%, and atomic percentage of Fe is 5%-40%; (3) performance optimization: calculating work function, elastic constant and thermal expansion coefficient of the alloy through first principle, adjusting composition based on calculation result, and determining final alloy composition; (4) smelting preparation: proportioning raw materials according to the final alloy composition, smelting raw materials through smelting process, and preparing alloy ingot; (5) subsequent processing: sequentially performing heat treatment and forming processing on the alloy ingot, and obtaining high-performance Cu-Ni-Fe alloy; In step (3), the work function of the alloy calculated through the first principle ranges from 4.5eV to 5.5eV, and the work function is the difference between the vacuum energy level and the Fermi energy level; In step (3), the calculation of the thermal expansion coefficient includes: constructing 11 alloy structure files with a scaling factor of 0.95-1.05, calculating the entropy, enthalpy, free energy and heat capacity data in the temperature range of 300K-2000K by the first principle, and determining the thermal expansion coefficient of the alloy in the temperature range of 300K-1200K <20×10 -6 / K; In step (3), the elastic constant satisfies that the bulk modulus K is 140GPa-190GPa, the shear modulus G is 35GPa-120GPa, the Young's modulus E is 90GPa-160GPa, and the Poisson's ratio v is 0.35-0.40; In step (4), the smelting process adopts vacuum arc smelting or induction smelting, the smelting temperature is 1400K-1800K, argon or nitrogen is introduced for protection during smelting, and the molten material is held for 10min-30min before casting; the raw material further contains trace elements with an atomic percentage of 0.1%-2%, and the trace elements are one or more of Ti, Zr or Mg.
2. The process for preparing high performance Cu-Ni-Fe alloy based on first-principles calculation design according to claim 1, characterized in that, In step (1), the Gibbs free energy model is a subregular solution model, and the thermodynamic parameter optimization includes model parameter fitting of liquid phase (L), (alphaFe) phase, (gammaFe, Ni) phase and (Cu, Ni) phase.
3. The process for preparing high performance Cu-Ni-Fe alloy based on first-principles calculation design according to claim 1, characterized in that, In step (2), the preliminarily determined alloy composition range is as follows: atomic percentage of Cu is 30%-75%, atomic percentage of Ni is 10%-30%, and atomic percentage of Fe is 10%-30%.
4. The process for preparing high performance Cu-Ni-Fe alloy based on first-principles calculation design according to claim 1, characterized in that, In step (5), the heat treatment process is holding at 873K-1273K for 1h-6h, and then cooling to room temperature in the furnace or air cooling to room temperature.
5. The process for preparing high performance Cu-Ni-Fe alloy based on first principles calculation design according to claim 1, characterized in that, In step (5), the forming processing is rolling, forging or extrusion, wherein the rolling temperature is 800K-1200K, and the reduction is 30%-70%.
6. The preparation process of high-performance Cu-Ni-Fe alloy designed based on first-principle calculation according to any one of claims 1-5, characterized in that, The high-performance Cu-Ni-Fe alloy has a tensile strength of greater than or equal to 816.4MPa and a total elongation at break of greater than or equal to 34.27%.
Citation Information
Patent Citations
Preparation method of Al-Ti-Zr alloy material having predetermined elasticity modulus
CN109439967A
preparation method of a Fe-Cu-C alloy material with predetermined hardness
CN109657382A
Multi-scale integrated temperature component phase diagram modeling method and device
CN116612842A
Computer-aided design method for synthesis process of Al-added copper-nickel alloy
CN118737336A
High-strength platinum-based multi-component solid solution alloy and design method thereof
CN120015195A
Cited By
Thermodynamic aided design of heat treatment process for Cu-Ni-Fe alloy
CN122256736A
Thermodynamic aided design of heat treatment process for Cu-Ni-Fe alloy
CN122256736B